The Study of L1 Interference on English Compositions Made by Eighth Graders - Maulida Yuniswati (ELLITE, 2017)
This study is aimed to find out the kinds of lexical and grammatical errorscaused by L1 interference or negative transfer of the mother tongue in writingcompositions made by eighth grade students of SMP Negeri 13 Malang andthe frequency of occurrence of errors. The focus of this study was identifying,describing, and classifying grammatical and lexical errors in students writing.Therefore, descriptive qualitative was considered appropriate for the design ofthe study. The subjects were 39 eighth grade students in 8A Class in the second semester of 2008-2009 academic years. The instrument used to collect the data was the students’ writing tasks. The result shows that there 586 errors resultingfrom L1 interference were found from 78 compositions. Some categories oferrors in Kwary and Sugiri could not be applied to the data, such as, if clause,embedded question, comparison, conjunction, and word class. No sentencescontaining those categories of errors were found in the data. However, theresearcher developed another category of errors that are not mentioned in theclassification scheme by Kwary and Sugiri, that is, clause without subject thatmakes up 2.56% of all errors.